2018
DOI: 10.7150/jca.26777
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Tumor Spread, Volume and Epstein-Barr Virus DNA in Nasopharyngeal Carcinoma: Feasibility of An Integrative Risk Stratification Scheme

Abstract: Purpose: To investigate the inter-correlation of tumor spread, volume and quantitative plasma Epstein-Barr virus DNA level (pEBV DNA), and to further assess the prognostic efficacy of a novel risk stratification combining anatomic, volumetric and biological features in nasopharyngeal carcinoma (NPC).Methods and Materials: One hundred and twelve patients with non-metastatic NPC were prospectively enrolled. Correlation of pEBV DNA with tumor invasiveness, lymph node (LN) metastasis, tumor volume and classificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
(32 reference statements)
1
2
0
Order By: Relevance
“…We also examined the baseline tumor size, blood CD8+ and CD4+ T cells proportions, and plasma IFN-γ levels in different response groups and did not observe a significant difference ( Figures 2C–F ; Supplementary Table S2 ). However, we found that plasma EBV DNA load was weakly related to tumor size (n=46, r=0.41, P = 0.0042) ( Figure 2G ), which was consistent with a previous study ( 35 ). However, we did not detect any correlations between plasma EBV DNA load and blood CD8+ T cell proportion, CD4+ T cell proportion, or TMB, using Spearman coefficient analysis ( Figures 2H, I ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…We also examined the baseline tumor size, blood CD8+ and CD4+ T cells proportions, and plasma IFN-γ levels in different response groups and did not observe a significant difference ( Figures 2C–F ; Supplementary Table S2 ). However, we found that plasma EBV DNA load was weakly related to tumor size (n=46, r=0.41, P = 0.0042) ( Figure 2G ), which was consistent with a previous study ( 35 ). However, we did not detect any correlations between plasma EBV DNA load and blood CD8+ T cell proportion, CD4+ T cell proportion, or TMB, using Spearman coefficient analysis ( Figures 2H, I ).…”
Section: Resultssupporting
confidence: 92%
“…Regarding environmental factors, we found that higher blood EBV DNA load was significantly related to poor clinical prognosis, as previously reported ( 41 ). Blood EBV load is often found to correlate positively with tumor size, reflecting that the cell-free EBV DNA likely originates from the tumor mass ( 35 ). Other than tumor size, the plasma EBV DNA load did not show correlation with the other identified markers (TMB, peripheral blood T helper cells and cytotoxic T cells, or IFN-γ levels).…”
Section: Discussionmentioning
confidence: 99%
“…In POLARIS-02 study, the association of baseline EBV DNA titers with ORR was not statistically different but patients with RM-NPC with low baseline EBV copy number had a significantly higher DCB rate and improved survival [ 5 , 20 ]. In our study, the baseline EBV load was positively correlated with tumor size and patients with PR and SD had significantly lower baseline EBV load than patients with PD, indicating that the blood EBV DNA might be derived from the tumor mass and could serve as an indicator of the tumor burden [ 29 ]. Previous studies have reported that large baseline tumor size was an independent prognostic marker of unfavorable efficacy in patients treated with pembrolizumab monotherapy [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%